Analisis Program Indonesia Sehat dengan Pendekatan Keluarga di Kecamatan Gadingrejo Kabupaten Pringsewu - Nila Arsita; Noverman Duadji (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2019)
Healthy Indonesia program with the approach of the family (PIS-PK) is intended to increase the degree of public health through health and community empowerment efforts are supported with financial protection and equitable health services. Implementation of PIS-PK is in fact outside the building health care Clinics. Through family visits, Team Clinics at once can provide early intervention against health problems that exist in every Member of the family. An expected data referable in conducting evaluations and interventions.Sub Gadingrejo Regency Pringsewu is one area which did not escape from the target program national PK PIS. During the implementation of the programme of the PIS-PK in Gadingrejo yet little-known by the public, so that the less response occurred at the beginning of the implementation of home visits. This research focuses on the problems of implementation of the programme of the PIS-PK as a health development efforts in Pringsewu Regency Gadingrejo. In order to reveal these problems, researchers using public policy implementation theory belongs to Van Meter and Van Horn, the kind of this research is descriptive research with qualitative approach. In this study it was found that the implementation of the programme of the PIS-PK are in the category of either Category either because it already has standards and a clear policy objectives and is scalable to support the success of the program in accordance with the expected goal, communication and coordination went smoothly, the characteristics of the implementing agency is in compliance with the objectives of the program, an attitude or disposition of implementing good environmental factors, social, economic and political support against the implementation of PIS-PK at Sub Gadingrejo.